2005
DOI: 10.1111/j.1366-9516.2005.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat complexity on forest beetle diversity: do functional groups respond consistently?

Abstract: We examined the responses of a beetle assemblage to habitat complexity differences within a single habitat type, Sydney sandstone ridgetop woodland, using pitfall and flight-intercept trapping. Six habitat characters (tree canopy cover, shrub canopy cover, ground herb cover, soil moisture, amount of leaf litter, and amount of logs, rocks and debris) were scored between 0 and 3 using ordinal scales to reflect habitat complexity at survey sites. Pitfall trapped beetles were more species rich and of different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
164
5
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 52 publications
10
164
5
8
Order By: Relevance
“…This suggests that each undisturbed habitat in the Ferret valley may be important for the conservation of certain dung beetle species. This is in accord with the idea that it is likely that a highly complex habitat may support more potential niches for a functionally diverse suite of species and a greater range of food webs than less complex habitats (Klopfer & MacArthur, 1960;Lassau et al, 2005). Tests conducted comparing a three-habitat scenario with a single-habitat scenario confirmed that the presence of numerous habitats is significantly associated with an increase in local dung beetle diversity.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that each undisturbed habitat in the Ferret valley may be important for the conservation of certain dung beetle species. This is in accord with the idea that it is likely that a highly complex habitat may support more potential niches for a functionally diverse suite of species and a greater range of food webs than less complex habitats (Klopfer & MacArthur, 1960;Lassau et al, 2005). Tests conducted comparing a three-habitat scenario with a single-habitat scenario confirmed that the presence of numerous habitats is significantly associated with an increase in local dung beetle diversity.…”
Section: Discussionsupporting
confidence: 75%
“…Habitat permanence, habitat complexity, resource availability, and diversity increase with successional gradient (Brown 1985). Habitat complexity was a powerful predictor of the species richness and abundance of pitfalltrapped beetles (Lassau et al 2005). GardiForest 10: 376-382 380…”
Section: Discussionmentioning
confidence: 99%
“…Shrub shading might be an important factor for their thermoregulation in the Mediterranean climate, characterized by hot and dry summer seasons. Middle and late successional stages dominated by shrubs and short trees might create optimal conditions for insect species, providing protection against adverse environmental conditions and predation, as well as greater levels of prey items (Lassau et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the soil is compacted and lacks humidity, which has promoted the disappearance of important taxa that were not present in MF such as beetles. This affected the functional processes of the ecosystem such as the reuse of matter, decomposition, herbivories feeding and predation, among others (Lassau, Hochuli, Cassis, & Reid, 2005).…”
Section: Pf Rfmentioning
confidence: 99%